Trends of in-hospital and ICU mortality in COVID-19 patients over the fourth and fifth COVID-19 surges in Iran: a retrospective cohort study from Iran. (26th July 2022) - Abdi, Sepideh; Nemati, Saeed; Nederi darbaghshahi, Nader; Mohammadi, Mehdi; Saeedi, Elnaz; Naji, Parnian; Taheri, Negar; Qandian, Ali; Joshang, Narges; Fattahi, Pedram; Namdar, Peyman; Vand rajabpour, Mojtaba
Abstract: Objective: The current study aimed to investigate the temporal trend of in-hospital and intensive care unit (ICU) mortality of coronavirus disease 2019 (COVID-19) patients over 6 months in the spring and summer of 2021 in Iran. Design: We performed an observational retrospective cohort study. Setting: Qazvin Province- Iran during 6 month from April to September 2021. Participants: All 14355 patients who were hospitalized with confirmed COVID-19 in hospitals of Qazvin Province. Intervention: No intervention. Main outcome measures: The trends of overall in-hospital mortality and ICU mortality were the main outcome of interest. We obtained crude and adjusted in-hospital and ICU mortality rates for each month of admission and over surge and lull periods of the disease. Results: The overall in-hospital mortality, early mortality and ICU mortality were 8.8%, 3.2% and 67.6%, respectively. The trend for overall mortality was almost plateau ranging from 6.5% in July to 10.7% in April. The lowest ICU mortality was 60.0% observed in April, whereas it reached a peak in August (ICU mortality = 75.7%). Admission on surge days of COVID-19 was associated with an increased risk of overall mortality (Odds ratio = 1.3, 95% confidence interval = 1.1, 1.5). The comparison of surge and lull status showed that the odds of ICU mortality in the surge of COVID-19 was 1.7 higher than in the lull period ( P -value < 0.001). Conclusions: We found that the risk of both overall in-hospital and ICU mortality increased over the surge period and fourth and fifth waves of severe acute respiratory syndrome coronavirus 2 infection in Iran. The lack of hospital resources and particularly ICU capacities to respond to the crisis during the surge period is assumed to be the main culprit.